2012
DOI: 10.1002/jmv.23267
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus‐associated hemophagocytic lymphohistiocytosis in Los Angeles County

Abstract: Data on Epstein–Barr virus‐related hemophagocytic lymphohistiocytosis (EBV‐HLH) in adults in the United States remain very limited. A cluster of four cases of EBV‐HLH was observed in a 4‐month period at a tertiary center in Los Angeles County (LA County) and the clinical and molecular characteristics identified in these cases are being described. EBV typing, immunophenotypic and molecular genetic studies were performed. Diagnostic criteria that may be used to identify EBV as a cause of HLH in adults are also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…59 While fulminant infectious mononucleosis may overlap with EBV-associated HLH, higher viral loads are seen in EBV-associated HLH. 54 While not as commonly reported nor as well defined as EBV, many other viruses may be associated with HLH. These can be best organized by DNA or RNA (ribonucleic acid) and, subsequently, by virus family, as listed in Table 2.…”
Section: Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…59 While fulminant infectious mononucleosis may overlap with EBV-associated HLH, higher viral loads are seen in EBV-associated HLH. 54 While not as commonly reported nor as well defined as EBV, many other viruses may be associated with HLH. These can be best organized by DNA or RNA (ribonucleic acid) and, subsequently, by virus family, as listed in Table 2.…”
Section: Infectionsmentioning
confidence: 99%
“…These studies have demonstrated that no single sub-strain of EBV has been linked to HLH as of yet. [54][55][56] It appears that new infection as well as reactivation of latent EBV infection may predispose individuals to HLH. Quantitative determination of EBV genome copy numbers in peripheral blood may be useful in predicting prognosis and effectiveness of therapy.…”
Section: Infectionsmentioning
confidence: 99%
“…The list of possible etiologies for secondary HLH is long and includes infections (mainly EBV, herpes simplex virus, cytomegalovirus, avian influenza) [2][3][4] , rheumatologic diseases (rheumatoid arthritis, systemic lupus erythemtosus, kawasaki disease, adult onset still's disease ) [5,6] , malignacy (natural killer cell leukemia, peripheral T cell lymphoma) [7,8] , acquired immune deficiency states (after organ transplants), and drugs [9] .…”
Section: Discussionmentioning
confidence: 99%
“…EBV infection has been the most commonly reported viral trigger for acquired HLH and the clinical characteristics vary from mild-to-severe; for its diagnosis, the patient must fulfil the HLH diagnostic criteria described in box 1. Antiviral therapy, intravenous immunoglobulin, rituximab and alemtuzumab have been used for patients who relapse, with haematopoietic stem cell transplantation if other therapies fail 7 13 22. There have also been a few reported cases of HLH after HAV infection.…”
Section: Discussionmentioning
confidence: 99%